[Rezension von: Thinking with St. John Paul II : JP2 lectures 2020/2021] - Hittinger, John (Philosophy & canon law, 2023)
A summary and reflection upon a series of lectures sponsored by the St. John Paul II Institute of Culture (Rome) by outstanding intellectuals from from Europe and the United States on a wide range of topics in the light of St. John Paul II's intellectual and spiritual legacy. Topics include culture, human work, foundations of ethics, art and beauty, the end of modernity, evangelization, and European identity.